2021
DOI: 10.1111/all.15042
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose pollen intralymphatic immunotherapy: Two RDBPC trials question the benefit of dose increase

Abstract: Background:The same dosing schedule, 1000 SQ-U times three, with one-month intervals, have been evaluated in most trials of intralymphatic immunotherapy (ILIT) for the treatment of allergic rhinitis (AR). The present studies evaluated if a dose escalation in ILIT can enhance the clinical and immunological effects, without compromising safety.Methods: Two randomized double-blind placebo-controlled trials of ILIT for grass pollen-induced AR were performed. The first included 29 patients that had recently ended 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 41 publications
(71 reference statements)
3
38
0
Order By: Relevance
“…ILIT involves injecting allergen extracts into a subcutaneous lymph node under ultrasound guidance and has been assessed in several recent studies. [106][107][108] Intra-lymph node injections of modular allergen translocation (MAT)-Fel d 1 vaccine (a major category of allergens) has been shown to induce allergen tolerance and promote cellular internalization of the allergen, inflammasome activation, and allergenspecific peripheral T-cell tolerance development. 109 However, this allergen preparation is still under investigation.…”
Section: Intralymphatic Immunotherapy (Ilit)mentioning
confidence: 99%
See 1 more Smart Citation
“…ILIT involves injecting allergen extracts into a subcutaneous lymph node under ultrasound guidance and has been assessed in several recent studies. [106][107][108] Intra-lymph node injections of modular allergen translocation (MAT)-Fel d 1 vaccine (a major category of allergens) has been shown to induce allergen tolerance and promote cellular internalization of the allergen, inflammasome activation, and allergenspecific peripheral T-cell tolerance development. 109 However, this allergen preparation is still under investigation.…”
Section: Intralymphatic Immunotherapy (Ilit)mentioning
confidence: 99%
“…110 In contrast, ILIT using tyrosine-adsorbed allergen extracts provided no profound therapeutic effects on AR symptoms induced by HDM, cat, or dog allergens. 111 It is noteworthy, however, that allergens may leak out of lymph nodes during injection 107 and drain rapidly into the venous system, possibly leading to adverse reactions. 112 Considering the comparatively small number of patients recruited for ILIT, the efficacy and potential adverse events of this form of therapy still need to be confirmed.…”
Section: Intralymphatic Immunotherapy (Ilit)mentioning
confidence: 99%
“…Most clinical trials were performed with commercially available medicine. One unsuccessful trial was performed with house dust mite, cat, or dog allergoids from Allergy Therapeutics LTD (Worthing, UK) [16] stabilized with microcrystalline tyrosine, and successful trials were performed with house dust mite allergoids from Allergopharma (Hamburg, DE) stabilized with glycerin [11] and with bee venom, grass and birch Alutard from ALK Abe ´llo ´(Hørsholm, DK) stabilized with aluminium hydroxide [4,5,12 && , 18,19,24]. One historic trial reported on early attempts to use a bee venom extract presently not registered [5].…”
Section: Allergen Extracts Usedmentioning
confidence: 99%
“…The most recent publication in [2] was Hellkvist et al [3]. Two publications presented more than one small, separate trial [4,5]. This unfortunate trend dilutes the impact of the individual trial.…”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that advances in immunotherapy technology will achieve greater efficacy and safety. AIT administration routes, adjunctive therapies, vaccine adjuvants and novel vaccine technologies are being pursued to achieve this goal [ 24 , 25 , 26 ]. Intra-lymphatic immunotherapy, component-resolved AIT, recombinant proteins, nanoparticles and virus-like particle vaccines, T- and B-cell peptides and allergoids are potential options to improve AIT effectiveness and reduce side effects.…”
mentioning
confidence: 99%